The mental representation of "If Only thoughts" : undoing the exceptionality effect - Dixon, James E. (Trinity College (Dublin, Ireland). School of Psychology, 2009)
The aim of this thesis is to investigate the mental representations and cognitive processes that underlie counterfactual 'if only' thoughts. We examine the exceptionality effect, the tendency to undo exceptional antecedents to an outcome. We test whether manipulating the mental representation of different possibilities affects its occurrence. In Chapter 1, we review the literature on counterfactual thinking, conditional reasoning and decision making.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin.